The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s00484-008-0151-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of evaporative cooling on the regulation of body water and milk production in crossbred Holstein cattle in a tropical environment

Abstract: The aim of this study was to determine how evaporative cooling modifies body function with respect to water metabolism and other variables relevant to milk synthesis in crossbred cattle. The study was conducted on two groups of 0.875HF:0.125RS crossbred Holstein cattle (87.5%) housed in an open-sided barn with a tiled roof (non-cooled animals) and in a close-sided barn under an evaporative cooling system (cooled animals). The maximum ambient temperature and relative humidity for the non-cooled group were 33 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
56
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 43 publications
7
56
0
1
Order By: Relevance
“…Similar results were previously described (McGuire et al 1991;Hirayama et al 2004;Chaiyabutr et al 2008). Other authors, in opposition to the aforesaid, reported that bovine somatotropin treatment, under heat stress, increased milk production, IGF-I release and RT in dairy cows (Sarko et al 1994;Jousan et al 2007).…”
Section: Time Sampling Datasupporting
confidence: 90%
See 3 more Smart Citations
“…Similar results were previously described (McGuire et al 1991;Hirayama et al 2004;Chaiyabutr et al 2008). Other authors, in opposition to the aforesaid, reported that bovine somatotropin treatment, under heat stress, increased milk production, IGF-I release and RT in dairy cows (Sarko et al 1994;Jousan et al 2007).…”
Section: Time Sampling Datasupporting
confidence: 90%
“…In the same way, while some authors have reported that growth hormone (GH) and insulin-like growth factor I (IGF-I) are negatively influenced by heat stress (Sarko et al 1994;Rhoads et al 2010;Wheelock et al 2010), others mentioned that IGF-I levels during heat stress are similar to those obtained within thermal comfort zone (McGuire et al 1991;Hirayama et al 2004;Chaiyabutr et al 2008;Collier et al 2008). For these reasons, the interactions between heat stress and CORT and between IGF-I and environmental heat remain controversial.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…All the meta-analyses were Castle and Watson, 1973;Castle and Thomas, 1975;Little et al, 1976;Holter et al, 1982;Murphy et al, 1983;Stockdale and King, 1983;Andersson et al, 1984;Woodford et al, 1984;Andersson, 1985;Janicki et al, 1985;Nocek and Braund, 1985;Richards, 1985;Anderson, 1987;Gorewit et al, 1989;Holter et al, 1990Shalit et al, 1991;Bahman et al, 1993;Dado and Allen, 1993, 1995, 1996Silanikove et al, 1997;Dahlborn et al, 1998;Dewhurst et al, 1998;Muller et al, 1994;Mooney and Allen, 1997;Burgos et al, 2001;Osborne et al, 2002aOsborne et al, , 2009Voelker and Allen, 2003;Cottee et al, 2004;Meyer et al, 2004;Taylor and Allen, 2005;Harvatine and Allen, 2006;Chaiyabutr et al, 2007Chaiyabutr et al, , 2008Thomas et al, 2007;Cardot et al, 2008;Kume et al, 2008Kume et al, , 2010Longuski et al, 2009;Kramer et al, 2009;Shapasand et al, 2010;Khelil-Arfa et al, 2012…”
mentioning
confidence: 99%